2021
DOI: 10.1080/2162402x.2021.1958589
|View full text |Cite
|
Sign up to set email alerts
|

Integrating CD4 + T cell help for therapeutic cancer vaccination in a preclinical head and neck cancer model

Abstract: Head and neck squamous cell carcinomas (HNSCC) are well suited for cancer vaccination strategies. In addition to tumor-associated antigens (TAAs) and endogenous retrovirus (ERV) encoded proteins, HNSCCs have a relatively high tumor mutational burden encoding potential neoepitopes. Peptide vaccine candidates are prioritized by predicted high-affinity to major histocompatibility complex (MHC) class I with MHC-II affinity largely not being considered. Herein, we extend previous studies to evaluate therapeutic vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Antigen-presenting cells (APC), such as dendritic cells (DC), take up these tumor antigens from circulation and present them to host T cells, leading to their activation and differentiation into effector T cells and memory T cells. Subsequently, the reactivated T cells (CTL) carry out tumor antigen -specific cytolytic activity ( ASIR ) by releasing cytokines such as interferon (IFN)-γ/tumor necrosis factor (TNF)-α, perforin, and granzyme, which eradicate cancer cells [ 18 , 19 ]. The T cell responses also include secreting IL-2, which supports cellular immunity, and increasing the expression of CD80/86 costimulatory signals, which are essential for T cell priming [ 19 ].…”
Section: Basic Principles Of Therapeutic Vaccinesmentioning
confidence: 99%
See 3 more Smart Citations
“…Antigen-presenting cells (APC), such as dendritic cells (DC), take up these tumor antigens from circulation and present them to host T cells, leading to their activation and differentiation into effector T cells and memory T cells. Subsequently, the reactivated T cells (CTL) carry out tumor antigen -specific cytolytic activity ( ASIR ) by releasing cytokines such as interferon (IFN)-γ/tumor necrosis factor (TNF)-α, perforin, and granzyme, which eradicate cancer cells [ 18 , 19 ]. The T cell responses also include secreting IL-2, which supports cellular immunity, and increasing the expression of CD80/86 costimulatory signals, which are essential for T cell priming [ 19 ].…”
Section: Basic Principles Of Therapeutic Vaccinesmentioning
confidence: 99%
“…Subsequently, the reactivated T cells (CTL) carry out tumor antigen -specific cytolytic activity ( ASIR ) by releasing cytokines such as interferon (IFN)-γ/tumor necrosis factor (TNF)-α, perforin, and granzyme, which eradicate cancer cells [ 18 , 19 ]. The T cell responses also include secreting IL-2, which supports cellular immunity, and increasing the expression of CD80/86 costimulatory signals, which are essential for T cell priming [ 19 ].…”
Section: Basic Principles Of Therapeutic Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although CTLs are potent in killing tumors, HTLs can directly exert antitumor effects through the production of cytokines such as IFN-γ, TNF-α, granzyme-B, and perforin [29][30][31]. Moreover, several reports have shown that HTLs are more important than CTLs in cancer immunotherapy by the direct tumor killing and education of CTLs or natural killer (NK) cells [32][33][34][35]. Because the support of HTLs to prime CTLs is only applied to high-avidity CTLs [36], high-avidity CTLs can be selectively activated with HTL epitopecombined CTL vaccines, whereas low-avidity CTLs compromise high-avidity CTLs with CTL vaccines alone.…”
Section: Selecting Tumor Antigens As a Source Of Vaccinesmentioning
confidence: 99%